A Theological Interpretation of Confucius’ Idea of “Great Unity” by the German Missionary Paul Kranz from a Cross-Cultural Perspective - HU, Ruiqin (Journal of Research for Christianity in China (JRCC), 2026)
The Confucian thought of "Great Unity" (Datong) in the world originates from the chapter "Li Yun" (The Evolution of Rites) in The Book of Rites and took shape during the Pre-Qin period. This thought not only embodies Confucius' praise and reverence for the golden age of ancient China, but also carries his vision and yearning for an ideal society in the future. Since the modern era, Paul Kranze, a German missionary and sinologist, has conducted a detailed study of Confucius and his thought of "Great Unity" based on Confucian classics such as the "Four Books and Five Classics", and put forward the unique view that "Confucius is a great prophet bestowed by God on the Chinese nation". The prophetic nature of Confucius is reflected in his clear recognition that he himself was a "not yet perfect" person—he was not the "Perfect sage" （“至圣者”）revered in The Doctrine of the Mean, but a prophet of the "Perfect sage"（“至圣者”）. The ideal of "Great Unity" outlined by Confucius has a deep inherent alignment with the core values of Christianity. In a certain sense, breaking down the spiritual barriers that hinder the exchange between Eastern and Western civilizations and striving to make all civilizations created by humanity shine together also vividly embodies the early exploration of the concept of "a community with a shared future for mankind".